Peran Kurikulum Muatan Lokal dalam Pembangunan Karakter Bangsa - Fazza Erwina Dwi; Bradley Setiyadi (STIKes Ibnu Sina Ajibarang, 2024)
Education plays an important role in shaping the character and identity of a nation. This article discusses how the local content curriculum serves to inject local values, ethics and morality into the learning process. By focusing on cultural identity and local values, local content education helps shape students' character and identity. In addition, the article discusses the difficulties and prospects for incorporating local content education into the national education system, and provides thoughts on how local content education can serve as a key pillar in the nation's character building.